Effects of the supernatant of Chlorella vulgaris cultivated under different culture modes on lettuce (Lactuca sativa L.) growth - Dai, Lin; Yu, Peng; Ma, Pengyao; Chen, Cheng; Ma, Jun; Zhang, Jinli; Huang, Bo; Xin, Zhikun; Zheng, Xufan; Tang, Tao (Frontiers in Nutrition, 2024)
CO2 capture by microalgae is a feasible strategy to reduce CO2 emissions. However, large amounts of cell-free supernatant will be produced after microalgal harvesting, which may be harmful to the environment if it is disorderly discharged. In this study, Chlorella vulgaris (C. vulgaris) was cultivated under three common cultivation modes (autotrophic culture (AC), heterotrophic culture (HC) and mixotrophic culture (MC)), and the obtained supernatant was used as fertilizer to investigate its effect on the growth of lettuce. The biomass concentration of C. vulgaris cultivated under MC and HC was 3.25 and 2.59 times that of under AC, respectively. The contents of macronutrients in supernatant obtained from AC were higher than those of MC and HC. However, the contents of amino acids and hormones in supernatant obtained from MC and HC were higher than those of AC. The fresh shoot weight, fresh root weight and root length of lettuce treated with supernatant were significantly higher than that of control treatment. In addition, the contents of chlorophyll, soluble sugar and soluble protein in lettuce treated with supernatant were also higher than that of control treatment. However, the contents of nitrate in lettuce treated with supernatant was lower than that of control treatment. These results showed that the supernatant could promote the growth of lettuce and was a potential of fertilizer for crop planting.